Dictionary of genocide - Totten, Samuel; Bartrop, Paul R. (Paul Robert) 1955-.; Jacobs, Steven L. 1947-.; Gale Group (Westport, Conn. Greenwood Press, 2008)
Identifies and explains the history and suffering of ethnic and religious groups experiencing genocide throughout the world. The people, places, governments, agencies, documents, legal terms, and all other aspects of genocide are defined.
v. 1. A-L -- v. 2. M-Z.
Electronic reproduction.
Keywords: Genocide -- History; Crimes against humanity -- History; Electronic books